Assessment of selected Physicochemical Parameters and Trace Metals in Street Dust along roads in Enugu Metropolis, Nigeria - B.C. Ichu; N. Abia-Bassey (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
Trace metals, present above permissible limits are an ever present threat to public health due to their toxicity and carcinogenic nature. They can also impair important biochemical processes in animals and affect plant growth. The assessment of these pollutants, commonly found in street dust, is important for environmental health quality. The present work investigated the level, sources and assessment of trace metal pollution in street dust along selected roads in Enugu metropolis. A total of 32 dust samples were collected from 10 major roads and analyzed for trace metal content with a Buck 210VGP AAS after strong tri-acid digestion. Values were obtained for 9 trace metals in the dust samples within the following ranges (in mg kg-1): Cr(0.67 - 3.67), Mn (2.33 - 7.67), Fe (408.33 - 512.33), Co (3.00 - 61.75), Ni (39.67 - 193.67), Cu (11.50 - 90.00), Zn (1.00 - 31.67), Cd (0.00 - 1.33), and Pb (0.00 - 46.67). pH values, electrical conductivity (EC) and total organic matter (TOM) of the samples ranged from 6.75 - 8.39, 556 - 578.67 μS/cm and 1.27 - 10.35% respectively. The geoaccumulation index (Igeo) shows moderate pollution of Cd and Pb in the roads. The integrated pollution index (IPI) also showed moderate to high level of pollution of the metals in the following order: Cu<Pb<Ni<Cd. Multivariate statistical analysis identified the major sources of these trace metals along the roads as vehicles (from parts and emissions) and road infrastructure.